الذات المتطرفة وإديولوجيا التمركز في الخطاب الروائي الجديد - خليل, سليمة (قــــــراءات; No 10 (2017): مجلة قراءات, 2019)
تسعى هذه الدراسة إلى استكناه جدلية العلاقة بين الذات المتطرفة والآخر المختلف الذي ترفضه وتكفره لاختلافه، لذلك تتبنى مقولات ورؤى نقدية تجاهه، وهذا كله يتم وفق فرض الإيديولوجية المركزية المتبناة داخل الخطاب الروائي. Abstract          This research aims to show deeply the controversial relation-ship between the extremist self and the different other extremely denied and disbelieved. So, it adopts sayings as well as critical visions towards it as a result of imposing ideology of ethnocentrism adopted within the novel’s speech